2002
DOI: 10.1039/b205835a
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of the isotopic composition of Sn using MC-ICP-MS

Abstract: High precision isotopic measurements of Sn in two commercially available high purity materials and a previously analysed cassiterite from Straits Settlement, Malaysia, are presented as a basis for a new measurement procedure using the Micromass IsoProbe MC-ICP-MS. The results show that under optimised instrumental conditions two laboratory calibration standard solutions (Johnson-Matthey Puratronic Grade 1 Sn metal foil and Specpure ICP/DCP Sn solution) are isotopically identical and an external reproducibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 18 publications
3
78
0
Order By: Relevance
“…For Sn isotopic analysis, on the other hand, the choice of internal standard is limited to Sb, as other elements with masses close to those of Sn isotopes give rise to isobaric interferences with some of the Sn isotopes (e.g., 112,114,116 Cd,115 In, 120,122,124 Te) [55]. Also in this case and for all of the ratios monitored during a measurement session lasting 10-12 h, the correlation recorded in ln-ln space was excellent (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For Sn isotopic analysis, on the other hand, the choice of internal standard is limited to Sb, as other elements with masses close to those of Sn isotopes give rise to isobaric interferences with some of the Sn isotopes (e.g., 112,114,116 Cd,115 In, 120,122,124 Te) [55]. Also in this case and for all of the ratios monitored during a measurement session lasting 10-12 h, the correlation recorded in ln-ln space was excellent (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although Loss et al (1990) observed small excesses of minor Sn isotopes in acid-etched residues, the discrepancy was attributed to analytical problems. At the same time, the variation in natural Sn isotope compositions in terrestrial samples has been of great interest to geochemists Jeffery, 1965, 1967;Rosman and McNaughton, 1987;McNaughton and Loss, 1990;McNaughton and Rosman, 1991;Clayton et al, 2002;Haustein et al, 2010). Among these studies, Haustein et al (2010) reported the largest Sn isotopic variation analysis for cassiterite samples by using MC-ICP-MS, with a view to future applications of Sn isotopes within archaeology.…”
Section: Introductionmentioning
confidence: 99%
“…The hydride formation rate estimated from a signal at mass of 125 and that of 124 Sn was less than 6 × 10 -6 . We also added a standard solution of Sb for mass bias correction (Clayton et al, 2002) such that the Sb concentration was 30 ppb.…”
Section: Tin Isotope Measurements By Mc-icp-msmentioning
confidence: 99%
See 2 more Smart Citations